Influence of climate on annual survival of Barn Swallows (Hirundo rustica) breeding in North America. (11th June 2014) - García-Pérez, Belén; Hobson, Keith A.; Albrecht, Gretchen; Cadman, Michael D.; Salvadori, Antonio
Abstract: Population dynamics of migratory birds are influenced by both local weather and larger-scale patterns in climate that can operate at various stages of their annual cycle. We investigated correlations between (1) annual climatic indices and weather during the breeding season and (2) the annual survival of Barn Swallows ( Hirundo rustica ) breeding at 2 sites in North America. Mark–recapture data collected during a 10-yr period for each of the 2 colonies in eastern and western North America were analyzed to model annual survival probabilities. Annual survival rates of Barn Swallows breeding in Seattle, Washington, USA, were higher in years preceded by El Niño Southern Oscillation (ENSO) winters and higher in years with more positive North Atlantic Oscillation (NAO) values. ENSO was expected to primarily influence wintering conditions through rainfall amount, and NAO was expected to influence climate on the breeding grounds; thus, climatic conditions on both breeding and wintering grounds likely affected the survival of these Seattle-breeding birds. By contrast, annual survival of swallows breeding in southern Ontario, Canada, remained constant over time and were not affected by any of the climatic parameters studied, which suggests that NAO did not have a strong effect on climatic conditions there and/or that these birds winter in regions where ENSO is not strongly correlated with local weather conditions. Alternatively, there may be less geographic variation in wintering-ground locations for Barn Swallows breeding in Seattle, resulting in stronger ENSO effects on survival for the Seattle population. Our results demonstrate how correlations between climate patterns on wintering grounds and annual survival can provide information on migratory connectivity at continental scales and underline the importance of local weather conditions throughout the annual cycle on survivorship and population dynamics of aerial insectivorous birds.